STRATEGI PEMBERANTASAN PENYAKIT CACINGAN PADA ANJING DI SEKITAR OBYEK WISATA SANUR DALAM UPAYA PENCEGAHAN PENULARANNYA YANG BERSIFAT ZOONOSIS - APSARI, IDA AYU PASTI; OKA, IDA BAGUS MADE; DAMRIYASA, I MADE; DWINATA, MADE (Buletin Udayana Mengabdi, 2012)
ABSTRACT The role of the dog as a definitive host for a number of zoonotic parasites has been recognized as a significant public health problem especially strey dog population. In this population, poor levels of hygine and overcrowding, together with the lack of veterinary attention and zoonotic awareness, exacerbates the risk of disease infection. A public service was undertaken on Friday 16th September 2005 in Sanur beach to control the dog parasitic zoonoses. About 30 trey dogs and 31 domesticated dogs were treated with anthelmintic to control the helminth infections. All of strey dogs were clinically in poor condition.